2014
DOI: 10.1111/ajo.12168
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of intra-uterine insemination versusin vitrofertilisation in patients with idiopathic or mild male infertility

Abstract: This study provides evidence that IVF is more successful and cost-effective than IUI using the same doses of FSH. Further confirmatory studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…130 Conversely, one small RCT demonstrated a benefit of IVF compared with expectant management in extensively pre-treated women, but the birth rate in the expectant management arm was very low 131 . IVF was more effective than unstimulated IUI 132,133 .…”
Section: [H1] Managementmentioning
confidence: 83%
“…130 Conversely, one small RCT demonstrated a benefit of IVF compared with expectant management in extensively pre-treated women, but the birth rate in the expectant management arm was very low 131 . IVF was more effective than unstimulated IUI 132,133 .…”
Section: [H1] Managementmentioning
confidence: 83%
“…The exclusion criteria included (1) recurrent miscarriage; (2) ovarian tumors/cysts; (3) atypical endometrial hyperplasia; (4) cervical intraepithelial neoplasm (CIN) I-III; (5) chromosomal abnormalities; (6) intrauterine adhesion and (7) cycles with donor sperm. The detail of patient screening was showed in (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Elzeiny evaluated the effects of IVF and IUI in couples with unexplained infertility when only 2-3 mature follicles were stimulated by the same dosage of gonadotropin. Their study demonstrated that the IVF group had a greater live birth rate and lower cost per live birth ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The OR for multiple pregnancy was 0.50 (95% CI: 0.04-5.53) for IUI without COS compared to SI and 2.00 (95% CI: 0.18-22.34) for IUI with COS compared to SI. One RCT with 102 women offered same-dose FSH stimulation and who developed two or three follicles were randomised 3:1 to IUI (n=33) or IVF (n=10) (Elzeiny et al ., 2014). IUI or IVF was performed 36h after hCG administration with single or double embryo transfer on day two yielded clinical pregnancy rates (40% vs. 12%, p =0.04) and live birth rates (40% vs. 6%, p =0.01) favouring IVF over IUI.…”
Section: Introductionmentioning
confidence: 99%